1988
DOI: 10.1143/jjap.27.l1775
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Al on Si by Gas-Temperature-Controlled Chemical Vapor Deposition

Abstract: Epitaxial Al(111) film was deposited on Si(111) by low-pressure chemical vapor deposition with the use of tri-isobutyl aluminum (TIBA) at the substrate temperature of 400°C with the deposition rete of 0.9 µm/min. It was necessary for epitaxy to preheat the TIBA gas just before the deposition on the substrate (gas-temperature controlling). The film surface was very smooth; reflectance was higher than 90%. Streaks were observed in RHEED patterns. The rocking curve measured by X-ray diffraction was very narrow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Hence, the minimal radii of via holes able to be filled by conformal deposition are restricted by the thinnest of the continuous Al films. This is the highest reflectance value among all reported CVD Al films, except epitaxial growth films, 16 to the authors' knowledge. As a result, the holes will not be filled with continuous film, and poor electrical conductivity between the top and bottom of the holes will be obtained.…”
Section: B Film Properties and Filling Propertiesmentioning
confidence: 61%
“…Hence, the minimal radii of via holes able to be filled by conformal deposition are restricted by the thinnest of the continuous Al films. This is the highest reflectance value among all reported CVD Al films, except epitaxial growth films, 16 to the authors' knowledge. As a result, the holes will not be filled with continuous film, and poor electrical conductivity between the top and bottom of the holes will be obtained.…”
Section: B Film Properties and Filling Propertiesmentioning
confidence: 61%
“…Al͑111͒/Si͑111͒ epitaxy was also reported with chemical vapor deposition at a substrate temperature of 400°C. 7 Heteroepitaxy of Al͑111͒ on Si͑111͒ requires accommodation of a 25% mismatch in their lattice constants. Based on high resolution cross-section transmission electron microscopy ͑TEM͒ of the Al/Si interface, it was concluded that Al͑111͒/ Si͑111͒ epitaxy with Al͓110͔/Si͓110͔ is accomplished by matching four Al planes to three Si planes.…”
mentioning
confidence: 99%
“…TIBA has been extensively studied as a precursor for deposition of Al films in the temperature range 200 o C -400 o C (Bent et al, 1989;Green et al, 1984;Kobayashi et al, 1988;Sekiguchi et al, 1988). The rate-determining step in the deposition of Al involves cleavage of the Al-C bond by a β-hydrogen elimination, but a competitive β-methyl elimination becomes significant at temperatures around 300 o C yielding C-contaminated films (Bent et al, 1989).…”
Section: The Mocvd Of Aluminum Thin Films 141 Precursors For Al Depositionmentioning
confidence: 99%